The Role of Mindfulness Training in Reducing Burnout in HR Teams during Digital Transformation - Parinsi, Welimas Kristina; Musa, Anugrah Dewi Lestari; Musa, Kartika Septiary Pratiwi (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study investigates the impact of mindfulness training on reducing burnout among Human Resource (HR) professionals in Makassar, Indonesia, amidst the pressures of digital transformation. Employing a phenomenological approach, the research explores lived experiences of HR personnel navigating technological change and their engagement with mindfulness practices. Findings reveal that digital transformation, while enhancing efficiency, exacerbates emotional exhaustion, technostress, and blurred work-life boundaries. Mindfulness training especially when culturally adapted to align with local values such as gotong royong and siri’ na pace proved effective in lowering stress levels and enhancing emotional regulation. However, the effectiveness of such interventions depends significantly on organizational support, including policies that prioritize well-being. The study advocates for integrated strategies combining cultural relevance and structural reform to foster sustainable resilience in Indonesia’s evolving work environments.